2018
DOI: 10.23937/2572-4010.1510021
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria among Newly Diagnosed Diabetic Patients at Mulago National Referral Hospital in Uganda: A Cross Sectional Study

Abstract: Background Microalbuminuria is an early marker of nephropathy, cardiovascular diseases and severe ocular morbidity in adults with diabetes mellitus. This subclinical condition is associated with high morbidity and mortality. Microalbuminuria precedes the development of overt diabetic nephropathy by 10–14 years. At this stage, one can reverse diabetic nephropathy or prevent its progression. Unfortunately, tests to detect microalbuminuria in diabetics are not routinely done in Uganda. This study sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…69 According to the current study, the overall pooled prevalence of MAU among diabetes patients in Africa was 37.11% (95% CI: 31.27-42.95). This finding indicated that a significant proportion 40 37.12 31.15-43.09 Muse et al (2020) 41 36.75 30.83-42.67 Ogiator et al (2020) 42 37.17 31.18-43.16 Ufuoma et al (2016) 43 36.37 30.66-42.09 Halliru et al (2016) 44 37.22 31.22-43.22 Erasmus et al (1992) 45 36.63 30.74-42.52 Bissong et al (2017) 46 37.20 31.21-43.18 Efundem et al (2017) 47 37.87 31.95-43.79 Rahamtalla et al (2012) 48 36.91 30.97-42.85 Lutale et al (2007) 49 37.92 32.03-43.82 Lutale et al (2007) 49 37.98 32.25-43.71 Ghosh et al (2012) 50 37.39 31.35-43.43 Kantarama et al (2021) 51 36.27 30.53-42.0 Martin et al (2018) 52 36.84 30.89-42.79 Martin et al (2018) 52 36.64 30.74-42.55 Kiconco et al (2019) 53 37.59 31.56-43.62 Lubwama et al (2022) 54 37.88 31.97-43.79 Kalk et al (2010) 55 37.04 31.08-43.0 Molefe et al (2018) 56 36.87 30.89-42.85 Ramaphane et al (2021) 57 37.41 31.39-43.44 Fetni et al (2021) 58 37.23 31.14-43.32 Fetni et al (2021) 58 37.03 31.09-42.98 Eghan et al (2007) 59 36.93 30.96-42.90 Amolo P (2010) 60 38.09 This pooled prevalence of MAU among type 2 diabetes patients is comparable to the findings (39%) of a global crosssectional study on type 2 diabetes patients conducted in 33 countries. 70 A similar result of 35.1% (12.3-74.5%) was reported in large, multiple international cohort studies including >3 million participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…69 According to the current study, the overall pooled prevalence of MAU among diabetes patients in Africa was 37.11% (95% CI: 31.27-42.95). This finding indicated that a significant proportion 40 37.12 31.15-43.09 Muse et al (2020) 41 36.75 30.83-42.67 Ogiator et al (2020) 42 37.17 31.18-43.16 Ufuoma et al (2016) 43 36.37 30.66-42.09 Halliru et al (2016) 44 37.22 31.22-43.22 Erasmus et al (1992) 45 36.63 30.74-42.52 Bissong et al (2017) 46 37.20 31.21-43.18 Efundem et al (2017) 47 37.87 31.95-43.79 Rahamtalla et al (2012) 48 36.91 30.97-42.85 Lutale et al (2007) 49 37.92 32.03-43.82 Lutale et al (2007) 49 37.98 32.25-43.71 Ghosh et al (2012) 50 37.39 31.35-43.43 Kantarama et al (2021) 51 36.27 30.53-42.0 Martin et al (2018) 52 36.84 30.89-42.79 Martin et al (2018) 52 36.64 30.74-42.55 Kiconco et al (2019) 53 37.59 31.56-43.62 Lubwama et al (2022) 54 37.88 31.97-43.79 Kalk et al (2010) 55 37.04 31.08-43.0 Molefe et al (2018) 56 36.87 30.89-42.85 Ramaphane et al (2021) 57 37.41 31.39-43.44 Fetni et al (2021) 58 37.23 31.14-43.32 Fetni et al (2021) 58 37.03 31.09-42.98 Eghan et al (2007) 59 36.93 30.96-42.90 Amolo P (2010) 60 38.09 This pooled prevalence of MAU among type 2 diabetes patients is comparable to the findings (39%) of a global crosssectional study on type 2 diabetes patients conducted in 33 countries. 70 A similar result of 35.1% (12.3-74.5%) was reported in large, multiple international cohort studies including >3 million participants.…”
Section: Discussionmentioning
confidence: 99%
“…For analysis purposes, studies done by Rahlenbeck et al, Martin et al, Lutale et al, and Fetni et al were extracted twice because they reported the prevalence of MAU separately for type 1 and type 2 DM. The studies were conducted in 14 different countries, including Ethiopia (2 studies), 40,41 Nigeria (6 studies), [42][43][44][45]66,67 Cameroon (3 studies), 46,47,64 Sudan (2 studies), 48,65 Tanzania (3 studies), [49][50][51] Uganda (2 studies), [52][53][54] South Africa (1 study), 55 Botswana (2 studies), 56,57 Algeria (1 study), 58 Ghana (1 study), 59 Kenya (1 study), 60 Egypt (1 study), 61 Senegal (1 study), 62 and Zambia (2 studies) 39,63 (Table 1).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Martin et al reported over 51% of their newly detected diabetic patients were males with mean age of 46 years in Uganda while Sosale et al reported over two-thirds being males in India. 19,20 Aboelnasr et al from Egypt reported two-thirds of newly detected diabetic patients being females and mean age was over 48 years. 21 Bansal et al reported female predominance of newly detected diabetic patients in another Indian report with mean age of nearly 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…The number of past episodes of DKA in each of the subjects was recorded. Microalbuminuria is defined as albumin to creatinine ratio (ACR) between 30 and 299 mg/g (7) However, it was assessed on the first morning using 5 mL of spot urine sample, collected in a clean plastic container. The ACR ratio was calculated in mg albumin/gm of creatinine.…”
Section: Methodsmentioning
confidence: 99%